2017
DOI: 10.5392/jkca.2017.17.01.351
|View full text |Cite
|
Sign up to set email alerts
|

Design and Implementation of a Flood Disaster Safety System Using Realtime Weather Big Data

Abstract: Recently, analysis techniques to extract new meanings using big data analysis and various services using them have been developed. A disaster safety service among such services has been paid attention as the most important service. In this paper, we design and implement a flood disaster safety system using real time weather big data. The proposed system retrieves and processes vast amounts of information being collected in real time. In addition, it analyzes risk factors by aggregating the collected real time … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…While several studies have confirmed these elements' independence and acknowledged their external impact. 12,13 Which has demonstrated how top management support may significantly aid in acquiring and applying innovative technologies, such as BDA. 113,114 Top management should play a crucial role in creating the necessary vision and later couple related strategies with associated alignment issues for generating business value from innovative technologies, as investigated by.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…While several studies have confirmed these elements' independence and acknowledged their external impact. 12,13 Which has demonstrated how top management support may significantly aid in acquiring and applying innovative technologies, such as BDA. 113,114 Top management should play a crucial role in creating the necessary vision and later couple related strategies with associated alignment issues for generating business value from innovative technologies, as investigated by.…”
Section: Discussionmentioning
confidence: 99%
“…14 BDAC has motivated organizations to provide cutting-edge and intelligent services while maintaining highly developed predictive skills. 13,15 These abilities allow organizations to make more intelligent business decisions, boost company performance, and contribute to sustainability. Even though there have been some BDA adoption success stories, many organizations have yet to fully understand the value of big data, their organizational readiness, and the technical requirements for such an investment.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations